Parasitic Lesions in Fish in the Federal District, Brazil - Ferreira Junior, Jair Alves; Cardoso, Saulo Pereira; da Fonseca, Nathália Dela-Sávia; Nascimento, Karla Alvarenga; Rodrigues, Fábio; da Rocha, Gino Chaves; Macêdo, Juliana Targino Silva Almeida e; Pedroso, Pedro Miguel Ocampos (Acta Scientiae Veterinariae, 2021)
Background: Brazil has a vast territory and favorable climatic conditions that allow the cultivation of freshwater fish. The intensification of the productive system can cause an imbalance in the aquatic environment as a result of poor water quality, nutritional deficiencies and infectious or parasitic diseases. The laboratory diagnosis and the determination of the prevalence of the main lesions, which occur in a certain region, help to guide towards the etiological diagnosis. This study aimed to describe the main parasitic lesions in fish in the routine at the Veterinary Pathology Laboratory of the Universidade de Brasília. Material, Methods & Results: All records of fish with parasitic lesions were recovered. Those cases in which there was an intralesional parasite and which presented lesions compatible with the parasite were included. The screening of ectoparasites was done by scraping the superficial mucus from the gills and skin. Organ sections were routinely processed for histopathologyand stained with hematoxylin-eosin (HE). In some records, parasitological identification was carried. The information was divided into the species of the affected fish, epidemiology of the outbreak (water quality, temperature, type of breeding), lesion distribution, etiology and macroscopic and microscopic changes. The resulting data was organized in absolute frequency and percentage. In this study, 22 cases were counted, between individual deaths and outbreaks, totaling 83 necropsied teleost fish.Inflammatory changes of parasitic origin were seen in 13/22 (59%) of the cases had lesions of parasitic origin. Skin lesions and gills were the most relevant. Macroscopically, red areas or spots of hyperemia or hemorrhage on the body surface were the most prevalent findings. Under microscopy, proliferative gill inflammation was the most relevant diagnosis. Pscinoodinium pilullare (Dinoflagellida), Ichthyophthirius multifiliis (Ciliophora), and monogenetic worms (Monogenea) were the main parasites found. Trichodina sp. (Ciliophora), Ichtyobodo sp. (Kinetoplastida), Amoebas, and Chilodonella sp. (Ciliophora), were seen in fewer numbers. An unusual case suggestive of parasitism by Eustrongylides sp. (Nematoda), in a pirá-brasília (Simpsonichthys boitonei), specimen has been recorded. Discussion: The diagnoses were based on epidemiology, anatomopathological and parasitological findings. The most frequent and significantly lethal lesion in the study was proliferative and / or hyperplastic branchitis. Proliferative branchitis with lamellar epithelial hyperplasia (LEH) is a response to some type of chemical or mechanical injury to the gill epithelium in order to protect the capillaries from further damage or microbial penetration. However, it also increases the diffusion distance between capillaries and the environment and, therefore, hinders breathing, excretory and osmoregulatory functions. Protozoan infections and monogenetic worms in general generated LEH and skin lesions of mechanical origin. Secondary bacterial infection, were observed in this parasitosis determining the cause of death of the fish. Its pathogenicity comes from the lesions caused by the colonization and histophagy of the epithelial surfaces, mainly gills and skin, causing epithelial proliferation, lamellar cell fusion, epithelial cell degeneration and necrosis forming several ulcers in the epithelium after the release of mature trophies. The pathogenesis of parasitism by Eustrongylides spp. is considerable when there is a large quantity of these larvae that can cause intestinal obstruction, rupture and compression of viscera, of greater importance in small fish. The main parasites of necropsied fish were protozoa and monogenetic worms, which mainly cause branquitis and dermatitis in varying grades.